2007
DOI: 10.1002/lt.21208
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-tryptophan-ketoglutarate solution vs. University of Wisconsin solution for liver transplantation: A systematic review

Abstract: University of Wisconsin (UW) solution has been recognized as the gold standard in liver preservation, but its limitations are becoming obvious, such as risk of biliary complications and its high cost. Alternatively, the effects of histidine-tryptophanketoglutarate (HTK), such as improved biliary protection and low cost, have been observed. This systematic review is conducted to compare the efficacy and safety of these 2 solutions. Databases from 1966 to June 2006 were searched. Randomized clinical trials (RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 38 publications
1
69
0
3
Order By: Relevance
“…Simultaneous graft revascularization seems to be associated with a lower incidence of ITBL than sequential revascularization [109,110] . Viscous preservation solutions may negatively impact on efficacy of flushing of the bile ducts capillaries, resulting in residual bile crystallization and obstruction [111][112][113] . Use of less viscous solutions, like HTK, seems to provide better results in reducing the incidence of biliary tract injuries, despite the recent results of the European liver transplant registry data [67,112] .…”
Section: Itblmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous graft revascularization seems to be associated with a lower incidence of ITBL than sequential revascularization [109,110] . Viscous preservation solutions may negatively impact on efficacy of flushing of the bile ducts capillaries, resulting in residual bile crystallization and obstruction [111][112][113] . Use of less viscous solutions, like HTK, seems to provide better results in reducing the incidence of biliary tract injuries, despite the recent results of the European liver transplant registry data [67,112] .…”
Section: Itblmentioning
confidence: 99%
“…Viscous preservation solutions may negatively impact on efficacy of flushing of the bile ducts capillaries, resulting in residual bile crystallization and obstruction [111][112][113] . Use of less viscous solutions, like HTK, seems to provide better results in reducing the incidence of biliary tract injuries, despite the recent results of the European liver transplant registry data [67,112] . In a large study, a CIT > 10 h was found to be associated with a higher incidence of ITBL and every effort should be made not to exceed this limit [113] .…”
Section: Itblmentioning
confidence: 99%
“…The reduced viscosity of HTK as compared to UW has been hypothesized to be protective against the development of biliary complications. However, the impact of HTK versus UW preservation on biliary complications remains unclear, as some centers report equivalent, increased or reduced rates of biliary complication with HTK preservation of deceased donor liver allografts (Feng et al, 2007;Steawart et al, 2009). …”
Section: Preservation Solutionsmentioning
confidence: 99%
“…In other research, both solutions have been tested and compared for different organs [35,36,37]. Reichenspurner et al [38] compared UW versus HTK solution for myocardial protection in heart transplantation.…”
Section: Review On Cooling Solutionsmentioning
confidence: 99%